The Influence of Understanding DSN-MUI Fatwa No. 116/DSN MUI/IX/2017 on the Implementation of Sharf Contracts in Sharia Electronic Money - Rahmawati, Widya; Hakim, Lukmanul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the effect of understanding DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017 on the implementation of sharf contracts in sharia electronic money services. The fatwa emphasizes the importance of the principle of taqabudh and the prohibition of riba in currency exchange transactions, including in the digital context. This study uses a quantitative approach with a survey technique on 56 respondents who use sharia electronic money services. The research instrument was tested for validity and reliability, with results showing that all statement items were valid and reliable. Normality and simple linear regression tests showed that the data were normally distributed and that there was a significant positive effect between understanding of the fatwa and the implementation of the sharf contract. These results reinforce the theory that a good understanding of sharia plays a role in increasing compliance with the principles of digital sharia transactions. The implications of this study encourage the strengthening of education on the principles of digital muamalah fiqh through DSN-MUI fatwas as a basis for the development of a sharia electronic money system.